Effect of Meconium Stained Liquor on Mode of Delivery and Fetomaternal Outcome in a Tertiary Level Hospital - Sultana, Rifat; Adhikary, Alpana; Hena, ShamsunNahar; Daisy, Nazia Sultana; Begum , Tahmina (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: The appearance of meconium-stained liquor during labour is generally considered to be a sign of hypoxia and a predictor of poor fetal outcome.It is one of the clinical events where normal pregnancy can turn into a high risk one for the mother as well as for the foetus. Objective: To evaluate the obstetric outcome in meconium stained liquor during labour. Study design: Prospective comparative study. Study setting and period: Gynaecology and Obstetrics department of Sir Salimullah Medical College and Mitford Hospital (SSMC and MH), Dhaka, between January 2019 to June 2019. Study population: The study patients in labour with meconium stained amniotic fluid and women in labour but having clear amniotic fluid who admitted for delivery during study period. Result: A total 75 cases were enrolled in the study as case and 75 cases were enrolled as control. The mean age was found 29.14±5.59 years in case group and 28.9±6.2 years in control group. Patients received irregular ANC was 20(26.7%) and 25(33.3%) in case and control group respectively. Patients who did not receive ANC was 24(32.0%) in case group and 12(16.0%) in control group. Mean gestational age at delivery was found 38.87±1.4 weeks in case group and 38.75±1.6 weeks in control group. Primigravida was predominant in both groups. Caesarean deliveries were high (80.0%) in cases and it was much higher with thick meconium (74.7%) as compared to thin meconium (25.3%). APGAR scores in first minute and fifth minute were also low in cases. Birth asphyxia was found 20.0% in case group and 6.3% in control group. Meconium aspiration syndrome 25.0% and convulsion 3.8% developed only in cases. Neonatal ward admission was 22.0% in case group and 6.3% in control group. Neonatal mortality was higher (3.8%) in cases than control 1.3%. Majority (6.65%) patients had post partum hemorrhage in case group and 3(4.0%) in control group. Conclusion: Meconium stained amniotic fluid were associated with higher rate of caesarian delivery, increased need for neonatal resuscitation, increased rate of birth asphyxia with hypoxic ischemic encephalopathy, meconium aspiration syndrome, hospital admission, and mortality. Electronic foetal monitoring, timely obstetrical intervention and neonatal care can reduce associated complications and improve foetal outcome. J Shaheed Suhrawardy Med Coll 2022; 14(1): 43-49